AD, Volume 2, n° 1, 1977 - Full Issue - BUJRA, Abdalla S. (Africa Development, 1977)
Contents Abdalla S. Bujra Editorial Note ........................ 5 Kwesi Botchwey Marxism and the Analysis of the African Reality ...................... 9 Résumé ........................ 16 Emmanuel Hansen Freedom and Revolution in the Thought of Frantz Fanon ........................ 17 Résumé ............................ 40 Jacques Depelchin African History and the ideological Reproduction of Exploitative Relations of Production ..................... 43 Résumé ....................... 61 Alain Cournanel Idéologie et Développement en Guinée ...................... 63 Summary ............................ 87 Michel Darnaud La problématique marginaliste, l'idéologie et l'avenir rwandais ..................... 89 Summary .............................. 103 FOCUS ON RESEARCH AND TRAINING INSTITUTES Institute of Development Management, Mzumbe, Tanzania ............................. 105 Institut Africain de Développement Economique et de Planification, Dakar, Sénégal .................... 111